2018
DOI: 10.18844/cjes.v13i4.3539
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of school leadership effects on student achievement in USA and Turkey

Abstract: This research study aims to investigate the effects of  school leadersip on student achievement in USA and Turkey. The method of meta-analysis is used to calculate the effect size of school  leadership on student achievement. 39 researches were included in the study. However, several publications included in the research have examined more than one leadership approach. Due to this reason, the dataset used in 39 publications was determined as 68 in total. The results of the analyses performed with a random effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
1
8
0
2
Order By: Relevance
“…The fourth moderator is the type of primary studies. Uysal and Sarier (2018) found that effect sizes reported in dissertations were larger than those in articles in Turkey, but the reverse was true in the US. Some meta-analysts argue that dissertations may exhibit a higher level of quality than articles and have even analysed dissertation data exclusively (Sun and Leithwood, 2012).…”
Section: Contextual and Methodological Moderatorsmentioning
confidence: 87%
See 2 more Smart Citations
“…The fourth moderator is the type of primary studies. Uysal and Sarier (2018) found that effect sizes reported in dissertations were larger than those in articles in Turkey, but the reverse was true in the US. Some meta-analysts argue that dissertations may exhibit a higher level of quality than articles and have even analysed dissertation data exclusively (Sun and Leithwood, 2012).…”
Section: Contextual and Methodological Moderatorsmentioning
confidence: 87%
“…However, secondary/high school teachers may be more qualified and therefore better able to support leadership initiatives. Meta-analytic results on the moderating influence of school grade levels are mixed (Chin, 2007; Karadag, 2020; Liebowitz and Porter, 2019; Marzano et al, 2005; Sun and Leithwood, 2012; Uysal and Sarier, 2018). The third moderator pertains to the source of leadership data used in primary studies.…”
Section: Contextual and Methodological Moderatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This ignores the impact of multiple leaders within schools on student learning (York-Barr and Duke, 2004). Third, most meta-analyses have not embraced more expansive definitions of student learning that include non-achievement outcomes (Chin, 2007; Karadag, 2020; Leithwood and Sun, 2012; Liebowitz and Porter, 2019; Sun and Leithwood, 2012; Uysal and Sarıer, 2018; Witziers et al, 2003). Lastly, existing meta-analyses (Chin, 2007; Karadag, 2020; Liebowitz and Porter, 2019; Sun and Leithwood, 2012; Uysal and Sarıer, 2018; Witziers et al, 2003) have not adequately considered school contextual moderators in investigations of leadership effects.…”
mentioning
confidence: 99%
“…Third, most meta-analyses have not embraced more expansive definitions of student learning that include non-achievement outcomes (Chin, 2007; Karadag, 2020; Leithwood and Sun, 2012; Liebowitz and Porter, 2019; Sun and Leithwood, 2012; Uysal and Sarıer, 2018; Witziers et al, 2003). Lastly, existing meta-analyses (Chin, 2007; Karadag, 2020; Liebowitz and Porter, 2019; Sun and Leithwood, 2012; Uysal and Sarıer, 2018; Witziers et al, 2003) have not adequately considered school contextual moderators in investigations of leadership effects. In particular, there are calls to reconceive school leadership from a social justice perspective to improve learning of lower-socioeconomic status (SES) students (Berkovich, 2014).…”
mentioning
confidence: 99%